2013
DOI: 10.1039/c3cc44075c
|View full text |Cite
|
Sign up to set email alerts
|

The G-triplex DNA could function as a new variety of DNA peroxidase

Abstract: This study is the first to investigate the interactions of hemin with a G-triplex DNA of T1 using different DNA binding assays. The low intrinsic peroxidatic activity of hemin could be significantly enhanced using T1. Furthermore, much decreased oxidation enhancement by T2 or T3 with one key guanine mutation was observed, and the observed peroxidatic activity of T1 should be directly due to the G-triplex complexed with hemin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…1b ). Of interest was that one of the G-rich sequences, TBA-3G, could form a G-triplex with two G:G:G triad planes 15 , 16 , while one of the non-G-rich sequences, HD28, could form a triplex containing both T:A-T and C + :G-C triplets 17 . The FLIM results showed that the fluorescence decay time of o -BMVC upon interaction with TBA-3G was 3.1 ns, which was longer than ~1.5 ns upon interaction with HD28 but was similar to the decay time upon binding to G4s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b ). Of interest was that one of the G-rich sequences, TBA-3G, could form a G-triplex with two G:G:G triad planes 15 , 16 , while one of the non-G-rich sequences, HD28, could form a triplex containing both T:A-T and C + :G-C triplets 17 . The FLIM results showed that the fluorescence decay time of o -BMVC upon interaction with TBA-3G was 3.1 ns, which was longer than ~1.5 ns upon interaction with HD28 but was similar to the decay time upon binding to G4s.…”
Section: Resultsmentioning
confidence: 99%
“…Given that TBA-3G was originally proposed as G4 folding intermediates of the TBA 18 , TBA-3G truncated from TBA was used to verify the presence of G-triplex 15 , 16 . Such G-triplex was also studied in human telomere 19 , 20 .…”
Section: Resultsmentioning
confidence: 99%
“…G-quadruplex has certain limitations in high background signal and the hybridized section is not easily unwound aer cleaved by EcoRI. 27,28 For example, undesired intermolecular G-quadruplex structures may form, and these structures may show high background interference. Recent reports found that G-triplex (G3) is a promising replacement for G-quadruplex.…”
Section: Introductionmentioning
confidence: 99%
“…This could provide more potential for diversifying nucleic acid structures since only three G‐tracts are needed in the G3 fold [25,26] . As for G4 structures, G3s have also found versatile applications in DNAzymes, [27,28] sensing devices, [29–32] and catalysis [33] . Various ligands (including metal complexes, [27,28,30] thioflavin T, [29,31] methylene blue, [32] bisquinolinium derivatives, [26] dihydropyrimidin derivatives, [34] porphyrins, [35] and isoquinoline alkaloids [36] ) were recognized to be able to interact with G3 structures.…”
Section: Introductionmentioning
confidence: 99%
“…As for G4 structures, G3s have also found versatile applications in DNAzymes, [27,28] sensing devices, [29–32] and catalysis [33] . Various ligands (including metal complexes, [27,28,30] thioflavin T, [29,31] methylene blue, [32] bisquinolinium derivatives, [26] dihydropyrimidin derivatives, [34] porphyrins, [35] and isoquinoline alkaloids [36] ) were recognized to be able to interact with G3 structures. In particular, we previously observed that the isoquinoline alkaloid of sanguinarine is efficient to initiate the unstructured 5′‐GGTTGGTGTGGTTGGTT‐3′ (TBA‐G3TT, a TBA‐G3 variant with an additional dinucleotide 5′‐TT‐3′ at the 5′ end) folding into a G3 monomer structure [36] .…”
Section: Introductionmentioning
confidence: 99%